International Investment Restrictions and Closed-End Country Fund Prices - Bonser-Neal, Catherine; Brauer, Greggory; Neal, Robert; Wheatley, Simon (Journal of Finance, 1990)
Some closed-end country funds trade at large premiums relative to their net asset values. This paper examines whether international investment restrictions raise country fund price-net asset value ratios by segmenting international capital markets. We test whether a relation exists between announcements of changes in investment restrictions and changes in these ratios using weekly data from May 1981 to January 1989. The results provide evidence that some foreign markets are at least partially segmented from the U.S. capital market.